Length – weight Relationships of Freshwater Fish Species in Kerian River Basin and Pedu Lake - Isa, Mansor Mat; Rawi, Che Salmah Md; Rosla, Rosalina; Shah, Shahrul Anuar Mohd; Shah, Amir Shah Ruddin Md (American-Eurasian Network for Scientific Information (AENSI), 2010)
The length-weight relationships of 12 freshwater fish species collected using various mesh size of gill nets and cast nets from Kerian River basin in Perak and Pedu Lake in Kedah were estimated. Devario regina, Rasbora sumatrana, Puntius binotatus, Labiobarbus lineatus, Cyclocheilichthys apogon and Crossocheilus oblongus were caught from the Kerian River and its tributaries. Meanwhile in the Pedu Lake, there were Puntius schwanenfeldii, Notopterus notopterus, Chela sp., Mystacoleucus marginatus, Osteochilus microcephalus, and Puntius gonionotus. Fish total length (TL) and standard length (SL) and weight were recorded. The values of constants a and b were determined from the length and weight data which transform into the linear equation of lnW=lna+blnL. These parameters were then fitted to the parabolic equation, W=aL . The length-weight relationships o b f fish from both areas were significantly different at P<0.001 and the growth exponents, b, for the fishes varied from 2.665 to 4.106. The values show that most of the fishes collected from the Kerian River basin were of positive allometric growth, while the fishes from the Pedu Lake were of negative allometric forms. Based on their scores of growth exponents, the fishes were grouped into light (b<3.0), heavy (b>3.0) or isometric (b=3) indicating poor, over and symmetric growths of length and weight respectively. Crossocheilus. oblongus (b=2.8854) in the Kerian River basin belonged to the light group as well as Chela sp. (b=2.6653), M. marginatus (b=2.7046) and P. schwanenfeldii (b=2.8635) from the Pedu Lake. The heavy group from the Kerian River basin were L. lineatus (b=2.9906), D. regina (b=3.3001), C. apogon (b=3.5162), R. sumatrana (b=3.6101) and P. binotatus (b=4.1063). Meanwhile, in the Pedu Lake, this group of fish included O. microcephalus (b=3.0541), P. gonionotus (b=3.2340) and N. notopterus (b=3.2500). The condition factor of D. regina reflecting its well being and degree of fatness, was compared in four Kerian River tributaries using the mean relative condition factor (Kn). Sungai Ijok provided a much better habitat for the fish with a Kn score of 1.2089±0.1882 followed by Sungai Mahang (1.0472±0.1671), Sungai Kangar (1.0212± 0.2295) and Sungai Selama (0.9105±0.1986). The fish habitat in Sungai Ijok was significantly different from those of Sungai Mahang and Sungai Selama and the habitats at the two latter rivers were statistically different from each other at P<0.05. The values of a, b and Kn varied with age and sex of the fish, wet and dry seasons, environmental conditions and water bodies as observed in the lotic and lentic environments of the Kerian River basin and Pedu Lake respectively.